Modern political analysis - "Dahl, Robert A." (Prentice Hall New Delhi, 2005)
"Modern Political Analysis by Robert A. Dahl and Bruce Stinebrickner (ISBN: 9788120328815) is a comprehensive examination of the foundational concepts and methodologies in political science. This edition delves into the nature of influence, the definition and scope of politics, and the characteristics of political systems. It offers a comparative analysis of political structures, distinguishing between polyarchies and non-polyarchies, and explores the reasons behind these differences. The book also addresses individual political participation and the processes of political evaluation. In light of significant global events, such as the September 11 attacks and the dissolution of the Soviet Union, the authors have updated the content to reflect contemporary political dynamics. The text concludes with a discussion on the relevance and application of modern political analysis in understanding current political phenomena.